Pollen viability in Syagrus romanzoffiana and S-coronata (Arecaceae) - Moro, F. V.; Silva, MAS; Moro, JR (International Society Horticultural Science, 1999)
Palms of the Syagrus genus have several natural hybrids in Brazil. They are widely cultivated around the world as ornamental palm. S. romanzoffiana is the parental of natural hybrids with other Syagrus species that are potentially useful as palm cultivated for heart of palm production. The objective of this work was to evaluate the pollen grains viability got from plants grown in the Experimental Nursery of the FCAVJ/UNESP, Jaboticabal, SP, Brazil. Pollen grains were sampled from inflorescence in three occasions: in the right day of anthesis, one day before and one day after anthesis. For each day, the inflorescence was subdivided in epical, medium and basal portions where pollen grains were collected. The results shown that: a) for S. coronata there was no statistical differences in pollen viability (pollen viability average = 92.89%); b) for S. romanzoffiana the average pollen viability was 87.27%, 87.47% e 86.85% before, during and after the anthesis, respectively. The basal portion pollen grains had lower viability (85.19% - p<0.01) than those from the medium (88.17%) and the apical (88.46%) portion of the inflorescence. These results shown that both species have no problems with pollen viability and can be used as parental of hybrids with other Syagrus species.